Please do help me with this question, **Thanks!**

\(\quad If\quad a+b+c=0,\quad then\quad find\quad \frac { { a }^{ 2 } }{ bc } +\frac { { b }^{ 2 } }{ ca } +\frac { { c }^{ 2 } }{ ab }\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestThe same question was in my FIITJEE package. :p

Anyway, Here's the solution.

I cannot type in LaTeX, because I am operating from my iPad.

Taking the LCM of the 3 terms to be added, we get,

(abc)(a^3+b^3+c^3)/(abc)^2

=(a^3+b^3+c^3)./(abc)

Now, Since a+b+c=0, a^3+b^3+c^3=3abc.

=3abc/abc=3. QED.

Method 2

Jugaad method. Try 1+1-2 :P

Log in to reply

:3 :3 :3 :3 :3 Cheers!

Log in to reply

Cheers! I hope you like the 2nd Method. :P

Log in to reply

The given expression can be converted to this,\[(a^3+b^3+c^3)/abc\].Now,because \(a+b+c=0,a^3+b^3+c^3=3abc\),hence answer is 3.Proof:\[a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca)\].

Log in to reply

Thank You!

Log in to reply

Most welcome!!

Log in to reply

You need to specify that \(a,b,c \in \mathbb R - \{0\} \) otherwise it would be undefined.

Log in to reply

Correct.I was also going to say that.

Log in to reply

Let \(a+b+c= \sigma_1 \\ ab+bc+ac=\sigma_2 \\ abc = \sigma_3 \\ \varphi_3 = a^3+b^3+c^3 \)

By Newton's sums we have:

\[\varphi_3=\sigma_1^3-3\sigma_1\sigma_2 + 3\sigma_3 = (0)^3-3(0)\sigma_2+3\sigma_3 = 3\sigma_3\]

The given expression can be written as : \(\dfrac{\varphi_3}{\sigma_3} = \dfrac{3\sigma_3}{\sigma_3} = \boxed{3}\)

Log in to reply

And is the Newton's Sum method easier than the usual method?

Log in to reply

It depends from person to person whether its easier or not.

Log in to reply

Log in to reply

Log in to reply

So Mr.Mathematician, @Nihar Mahajan ,

Thank U, but Can you tell me what are Newton's sum or provide a link to it so that I learn about them?Log in to reply

Click here for Newton's identities and click here too :).

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

@Pi Han Goh where did u get the link. How many hours do u stay online on brilliant @Nihar Mahajan ??

Lol :P.Log in to reply

Log in to reply

Log in to reply

Such questions r in class 9 RD Sharma book.

Log in to reply

If a+b+c=0 Then,a^3+b^3+c^3-3abc=0 Therefore,a^3+b^3+c^3=3abc

Now in the question ,LCM of denominators will be "abc''

Thus ,on the numerator we get,a^3+b^3+c^3

Which is equal to 3abc

Therefore substituting it,we get the answer as 3...

Answer::3

Log in to reply

Thank You!

Log in to reply